The management of insects in recreation and tourism - Lemelin, Raynald Harvey (Cambridge University Press, 2012)
"Insects such as cockroaches, mosquitoes and bed-bugs are usually not highly sought amongst travellers or recreationists, yet each year, collectors, butterfly enthusiasts, dragonfly-hunters and apiarists collect, visit, document and raise insects for recreational purposes. Illustrating a range of human-insect encounters from an interdisciplinary perspective, this book provides the first insight into the booming industry of insect recreation. Case studies and examples demonstrate the appeal of insects, ranging from the captivating beauty of butterflies to the curious fascination of locust swarms, and challenge the notion that animals lacking anthropomorphic features hold little or no interest for humans. Throughout the book, the emphasis is on the innovators, the educators, the dedicated researchers and activists who, through collaboration across fields ranging from entomology to sociology and anthropology, have brought insects from the recreational fringes to the forefront of many conservation and leisure initiatives"--